2005
DOI: 10.1111/j.1365-3180.2004.00422.x
|View full text |Cite
|
Sign up to set email alerts
|

Life cycle and potential gene flow of volunteer oilseed rape in different tillage systems

Abstract: Summary The study examined the effect of tillage (intensive vs. zero tillage) on potential gene flow during the life cycle of oilseed rape volunteers between July 2002 and August 2003. After growing oilseed rape, 4–29% of the seeds lost during harvest entered the soil seedbank when stubble tillage was performed immediately after the seed input. The seedbank was small (0–3%) when stubble tillage was delayed. Zero tillage resulted in seedbanks from 1 to 17% of the initial seed input. The seeds were distributed m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 21 publications
(44 reference statements)
1
33
0
Order By: Relevance
“…In Europe, contradicting results have been reported. In one study, Gruber et al (2004a) reported some overlap of flowering periodicity between cropped and volunteer winter B. napus, while in a different study (Gruber et al 2005), volunteers flowered one month later than a winter canola crop sown at the typical time.…”
Section: Historymentioning
confidence: 99%
“…In Europe, contradicting results have been reported. In one study, Gruber et al (2004a) reported some overlap of flowering periodicity between cropped and volunteer winter B. napus, while in a different study (Gruber et al 2005), volunteers flowered one month later than a winter canola crop sown at the typical time.…”
Section: Historymentioning
confidence: 99%
“…Canola seeds can enter the soil seed bank when they are buried by tillage (Gruber et al 2005) and achieve secondary dormancy under sub-optimal germination conditions, such as water stress and darkness (Pekrun et al 1997;Lo´pez-Granados and Lutman 1998). Temperature is also a factor in the process of germination of canola populations (King et al 1986;Squire et al 1997), with a genetic basis for temperature-dependent germination and secondary dormancy of specific sub-populations (Marshall et al 2000).…”
mentioning
confidence: 99%
“…Any tillage operation shortly after oilseed rape harvest should be avoided. Rather, seeds should stay on the untilled ground for a longer period of time to prevent them from falling dormant and to increase seed mortality (Pekrun et al 1998, Gruber et al 2005. Consequently, only a few volunteers should be expected in the following crop, especially after inversion tillage.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, only a few volunteers should be expected in the following crop, especially after inversion tillage. Using conventional tillage systems, only 21 (Lawson et al 2006), 1.3 (Gruber et al 2005), and 8.8 (Gruber & Claupein 2008) volunteers m -2 were counted. If low disturbance tillage with direct-seeding is applied, the possible number of volunteers emerging in wheat can be very high with a maximum of nearly 1300 (Lawson et al 2006).…”
Section: Discussionmentioning
confidence: 99%